2016
DOI: 10.3389/fmicb.2016.01339
|View full text |Cite|
|
Sign up to set email alerts
|

All Three Endogenous Quinone Species of Escherichia coli Are Involved in Controlling the Activity of the Aerobic/Anaerobic Response Regulator ArcA

Abstract: The enteron Escherichia coli is equipped with a branched electron transfer chain that mediates chemiosmotic electron transfer, that drives ATP synthesis. The components of this electron transfer chain couple the oxidation of available electron donors from cellular metabolism (e.g., NADH, succinate, lactate, formate, etc.) to the reduction of electron acceptors like oxygen, nitrate, fumarate, di-methyl-sulfoxide, etc. Three different quinones, i.e., ubiquinone, demethyl-menaquinone and menaquinone, couple the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 57 publications
5
48
0
Order By: Relevance
“…It is known that specific strains of E. coli do vary in having nitrate reductase which is most active under anaerobic conditions (Potter et al 1999). Similarly, authors have shown that anaerobic conditions may be important as triggers to nitrate reductase, hence nitrate utilization (Ishimoto and Yamamoto 1977;Noguchi et al 1997;Whitehead and Cole 2006;Warry et al 2008;van Beilen and Hellingwerf 2016). Again, the type of strain used may play a significant role as nitrate utilization is strain specific.…”
Section: Growth and Nutrient Utilization After 24 H Sodium Nitrate Exmentioning
confidence: 99%
“…It is known that specific strains of E. coli do vary in having nitrate reductase which is most active under anaerobic conditions (Potter et al 1999). Similarly, authors have shown that anaerobic conditions may be important as triggers to nitrate reductase, hence nitrate utilization (Ishimoto and Yamamoto 1977;Noguchi et al 1997;Whitehead and Cole 2006;Warry et al 2008;van Beilen and Hellingwerf 2016). Again, the type of strain used may play a significant role as nitrate utilization is strain specific.…”
Section: Growth and Nutrient Utilization After 24 H Sodium Nitrate Exmentioning
confidence: 99%
“…MK levels are known to be tightly linked to the redox potential in bacteria (2,3,(7)(8)(9)(10); however, the molecular mechanisms that regulate this phenomenon are unclear. The first committed step in MK biosynthesis in Mtb is catalyzed by the thiamine diphosphate (ThDP)-dependent enzyme MenD (2-succinyl-5enolpyruvyl-6-hydroxy-3-cyclohexadiene-1-carboxylate synthase, SEPHCHC synthase).…”
mentioning
confidence: 99%
“…Recently, it has been reported that a third type of quinone (demethyl menaquinone) is involved in ArcB phosphorylation modulation. It seems that demethyl menaquinone is also able to oxydize ArcB and that demethyl menaquinol is able to reduce ArcB (376).…”
Section: A Indirect Redox Sensing Based On Pas-gaf Domainsmentioning
confidence: 99%